In the Wild HRI Scenario: Influence of Regulatory Focus Theory - Agrigoroaie, Roxana; Ciocirlan, Stefan-Dan; Tapus, Adriana (Frontiers in Robotics and AI, 2020)
Research related to regulatory focus theory has shown that the way in which a message is conveyed can increase the effectiveness of the message. While different research fields have used this theory, in human-robot interaction (HRI), no real attention has been given to this theory. In this paper, we investigate it in an in the wild scenario. More specifically, we are interested on how individuals react when a robot suddenly appears at their office doors. Will they interact with it or will they ignore it? We report the results from the approach of 42 individuals. Twenty-nine of them interacted with the robot, while the others either ignored it or avoided any interaction with it. The robot displayed two types of behavior (i.e., promotion or prevention). Our results show that individuals that interacted with a robot that matched their regulatory focus type interacted with it significantly longer than individuals that did not experience regulatory fit. Other qualitative results are also reported, together with some reactions from the participants.